The Effects of Fish Omega-3 Fatty Acids By Gavage on Some Metabolic Enzymes of Rat Testes - Sarsılmaz, Mustafa; Yılmaz, H. Ramazan; Songur, Ahmet; Türkoğlu, Aslı Ö.; Akyol, Ömer (Fırat University, 2003)
Aim: The aim of this study was to investigate the effect of fish omega-3 fatty acids on some metabolic enzymes of rat testes. Material and method: Wistar albino rats were divided into two groups. Rats of experimental group (n=9) were supplemented fish omega-3 fatty acids as 0,4g/kg bodyweight by gavage for 30 days in addition to their normal diet. Isotonic solution was given to the control group (n=8) by the same way. At 30th day, the rats were killed by decapitation under ether anesthesia, autopsied and testes was removed. Spectrophotometric methods were used to determine the activities of glucose-6-phosphate dehydrogenase (G6PD), 6-phosphogluconate dehydrogenase (6PGD), lactate dehydrogenase (LDH), malate dehydrogenase (MDH) and hexokinase (HK) enzymes in the testes tissues. Results: The fish omega-3 fatty acids caused increases in the activities of G6PD, 6PGD, LDH, MDH, and HK in comparison with control. In the MDH increase was statistically significant. Conclusions:Omega-3 fatty acids increase the HK, G6PD, 6PGD, and LDH enzyme activities insignificantly and MDH enzyme activity significantly. The mechanism of this effect is not clear. We suggested that omega-3 fatty acid affects energy protection system positively by increasing MDH enzyme activities, which is a member of energy protection cycle.

Amaç: Balık omega-3 yağ asitlerininin sıçan testisindeki bazı metabolik enzimlerin aktiviteleri üzerine olan etkisini incelemektir. Gereç ve yöntem: Albino Wistar cinsi sıçanlar iki gruba ayrıldı. Deney grubundaki sıçanlara (n=9) standart yemlerine ek olarak 0,4 g/kg vücut ağırlığı dozu olacak şekilde balık omega-3 yağ asitleri 30 gün süreyle gavaj yolu ile verildi. Kontrol grubuna (n=8), serum fizyolojik aynı yolla verildi. Otuzuncu günde anestezi ile dekapite edilen sıçanlardan testisler çıkarıldı. Testis dokusunda, glukoz-6-fosfat dehidrogenaz (G6PD), 6-fosfoglukonat dehidrogenaz (6PGD), laktat dehidrogenaz (LDH), malat dehidrogenaz (MDH) ve hekzokinaz (HK) enzim aktiviteleri spektrofotometrik olarak tayin edildi. Bulgular: Balık omega-3 yağ asitlerinin kontrol grubuna göre, MDH enzim aktivitesinde istatistiksel olarak önemli bir artışa neden olduğu gözlendi. G6PD, 6PGD, HK ve LDH enzim aktivitelerinde ise, kontrol grubuna göre anlamlı bir fark bulunmadı. Sonuç: Balık omega-3 yağ asitleri sıçan testis HK, G6PD, 6PGD ve LDH enzim aktivitelerini anlamsız bir şekilde ve MDH enzim aktivitesini anlamlı bir şekilde artırmasının mekanizması bize göre henüz kesin olmasa da, MDH enziminin enerji üreten bir siklusun üyesi olması, balık omega-3 yağ asitlerinin enerji üretim sistemini olumlu yönde etkileyebileceği konusunda fikir vermektedir. Bunun da sperm maturasyonu ve canlılığının korunmasında etkin olabileceği düşünülebilir.
Balık Omega-3 Yağ Asitlerinin Sıçan Testisinde Bazı Metabolik Enzim Aktiviteleri Üzerine Etkisi